ابداع وسائل تعليم اللّغة العربية في مدرسة الإصلاح المتوسّطة الإسلامية بوكيت تنجي - Majidah, Luthfia; Dewi, Yelfi; Husni, Arman; Anas, Al Baihaqi (Darul Yasin Al Sys, 2023)
The problem of this research is the means of teaching and its creative methods in teaching the Arabic language to the eighth grade students in Al-Islah Islamic Intermediate School in Bukit Tinggi because the Arabic language teacher has used different methods that affect the students' grades and improve students' understanding in teaching the Arabic language. The objectives of this research are to find out the forms, application and benefits of creating Arabic language teaching methods at Al-Islah Islamic Intermediate School in Bukit Tinggi. In this research, the researcher used descriptive qualitative research. Then the researcher used the qualitative approach by describing the data obtained by the researcher as a result of the research. As for the sources of information to provide data related to the research, they are the Arabic language teacher in the eighth grade and the eighth grade students. The research tools used in this research are observation, interview and documentation. The results of this research are the forms of innovation of means of teaching the Arabic language, its application and its benefits in Al-Islah Islamic Intermediate School, Bukit Tinggi.